KAWIN BEDA AGAMA DAN PERLINDUNGAN HAM : STUDI KRITIS ATAS UNDANG-UNDANG PERNIKAHAN NOMOR 1 TAHUN 1974 DAN UNDANG-UNDANG DASAR 1945 - Yedi Purwanto (Faculty of Sharia and Law, Sunan Gunung Djati Islamic State University of Bandung, 2015)
The polemic of Marriage Law Number 1 of 1974 is back into hot issue to be discussed. It reminds to the public discussion in a long history and the dynamics of the appearance of this laws. This time, the spotlight is article 2, paragraph 1 of the Marriage Law Number 1 of 1974 which contains